Parental Involvement Management And Its Contribution To Student Discipline At Elementary School 6 Muara Telang - Eri Wahyudi; Mahasir Mahasir; Wahid Ibrahim Banul Ngindom (International Journal of Social Sciences and Humanities, 2026)
This study aims to analyze the implementation level of Parental Involvement Management (PIM) at SDN 6 Muara Telang , reviewed through the POAC functions (Planning, Organizing, Actuating, Controlling) and Epstein's six types of parental involvement. It also measures the discipline level of fourth- and fifth-grade students in terms of time discipline, compliance with school rules, and learning responsibility, as well as examining the significant relationship between PIM and student discipline. The research employed a quantitative approach with a survey method. The sample was determined using proportional random sampling involving students and their parents. Data were collected through questionnaires and analyzed using SPSS with multiple regression, t-test, F-test, and coefficient of determination (R²). The findings reveal that the variable PIM_X1 (parental involvement in managerial aspects) does not significantly affect student discipline, indicated by a t-test significance value of 0.437 (> 0.05). Conversely, the parental contribution variable (X2) has a significant positive effect, with a t-test significance value of 0.000 (< 0.05), a regression coefficient of 0.553, and a standardized Beta of 0.634. The regression model obtained is Y = 45.808 + 0.078X1 + 0.553X2. The F-test result shows an F-value of 41.711 with a significance of 0.000, while the R² value of 0.476 confirms that both independent variables explain 47.6% of the variation in student discipline. Thus, parental contribution proves to be more dominant than managerial involvement in shaping student discipline at SDN 6 Muara Telang.